The mediating effect of employee’s trust on e-government and good governance in the public sector of developing countries - Alaaraj, Hassan; Ibrahim, Fatimah Wati (Macrothink Institute, 2014)
The main purpose of this paper is to study the mediating effect of employee‟s trust between e-government and good governance in the public sector of the developing countries.In addition, it presents a conceptual research framework to understand these relationships supported by literature review from recent studies.The main findings indicate that empowering public sector employees through practicing e-government creates trustworthy behaviors which are necessary to promote effectiveness, efficiency, transparency and innovativeness as means of good governance. Implications and limitations of the study are also discussed where future studies are recommended to extend the research empirically and highlight more on governments of developing countries which are in need to such kind of transformation for an effective economic reform